Pelatihan Penelitian Tindakan Kelas bagi Alumni Pendidikan Biologi Sebagai Upaya Peningkatan Kompetensi Profesional Guru - Yusnaeni Yusnaeni; Andam, S. Ardan; Moses. K. Tokan; Angela, G. Lika; Mbing. M. Imaculata; Nikmah Nikmah; Paulus Taek; Mario. J. Santrum; Sudirman Sudirman (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2023)
The quality of teachers is a problem faced in the world of education. Quality teachers can be achieved when teacher professionalism is formed. Professional teachers are teachers who have a number of competencies, namely: pedagogic, personality, social, and professional competencies. One way to improve teacher quality is to ensure that teachers reflect and make continuous improvement through classroom action research training. This service aims to deepen the knowledge and appreciation of prospective teachers about how to think and work collaboratively in solving problems in the classroom and to train skills in conducting classroom action research. Activities are carried out using Participatory Learning and Action (PLA) and Community Empowerment (CE) approaches using extension methods (lectures and discussions), practice, and mentoring. The results of the service implementation activities showed a very enthusiastic response for prospective teacher alumni where they wanted this kind of activity to be carried out regularly and if possible in a larger scope. From the results of the analysis of the results of the pre-test, it was revealed that the knowledge of the Alumni about CAR was not complete and still mixed with the type of quasi-experimental research. On the other hand, it was also revealed that knowledge about the instruments and observers in CAR was still minimal. After being given a detailed explanation by 5 presenters, they understood it, where almost 100% of the participants had correctly answered questions about CAR. Keywords: Professional, Competence, Classroom Action Research